Students' Learning Difficulties In English Subjects; Case Study In SMA Muhammadiyah Padang Panjang - Rini Hendrita; Ririn Kurnia (Inovasi Pendidikan, 2025)
This research analyzes the students’ difficulties in learning English. It uses descriptive qualitative research. The sample of this research was the students of class X SMA Muhammadiyah Padang Panjang. The data collection instrument used a questionnaire. The results of this study show the difficulties in learning English. From the data obtained, the difficulties experienced by students when learning English were lack of self- confidence, low concentration, and low memory. Students who have low confidence in learning English find it difficult to understand when the teacher speaks English